2013
DOI: 10.1002/j.2205-0140.2013.tb00106.x
|View full text |Cite
|
Sign up to set email alerts
|

A pictorial guide for the second trimester ultrasound

Abstract: Introduction: The second trimester ultrasound remains an important screening tool for detecting fetal abnormalities. This pictorial guide for the second trimester ultrasound is designed to assist practitioners to produce a high quality diagnostic survey of the fetus by demonstrating and describing recommended images. Methods: Each image is discussed in detail and has an associated drawn line diagram to aid in the identification of the important features of that image. There is a description of the salient land… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 49 publications
0
38
0
Order By: Relevance
“…The systematic review by Ruiter et al demonstrated 83% of vasa praevia cases had one or more clinical risk factors, highlighting that occasionally, a vasa praevia case will have no detectable risk factors. Screening every woman in the mid‐trimester ultrasound transabdominally over the lower uterine segment with colour Doppler should improve the detection in these cases (Figures and ) …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The systematic review by Ruiter et al demonstrated 83% of vasa praevia cases had one or more clinical risk factors, highlighting that occasionally, a vasa praevia case will have no detectable risk factors. Screening every woman in the mid‐trimester ultrasound transabdominally over the lower uterine segment with colour Doppler should improve the detection in these cases (Figures and ) …”
Section: Discussionmentioning
confidence: 99%
“…Surveyed participants definition of vasa praevia should improve the detection in these cases (Figures 6 and 7). 2,10 The prevalence of velamentous cord insertion is the most common cause of vasa praevia and occurs in 1:100 singleton pregnancies. 7,[11][12][13] The number of women with a velamentous cord insertion that will have a vasa praevia has been reported high as 1 in every 13.…”
Section: Figurementioning
confidence: 99%
“…A dynamic sweep of the transducer with colour Doppler over the lower uterine segment (to the lateral uterine walls) should be performed and documented at every mid trimester ultrasound 2,3,6 A visible risk factor, poor visualisation or potential fetal vessel in the lower uterine segment should prompt a transvaginal ultrasound as it has a higher specificity and improved accuracy than transabdominal approach 2,3,7 The location of the placental cord insertion should be identified at every mid trimester ultrasound with 2D imaging and colour Doppler 3 .…”
Section: Recommendationsmentioning
confidence: 99%
“…If a velamentous cord insertion is detected further investigation with transvaginal ultrasound of the lower uterine segment to exclude vasa praevia is recommended 2‐4 Universal screening of the placenta architecture is recommended at every mid trimester ultrasound 7 . If a succenturiate lobe placenta is identified, documentation of communicating vessels between the two placental components is advised.…”
Section: Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation